A new species of Goniurosaurus from Hainan Island, China based on molecular and morphological data (Squamata: Sauria: Eublepharidae) - Zhu, Xiao-Yu; Shen, Chu-Ze; Liu, Yun-Fei; Chen, Lin; Li, Zheng; He, Zhu-Qing (Zootaxa, 2020)
Three species of geckos in the genus Goniurosaurus have been recorded from Hainan Island in China. We describe a new species, Goniurosaurus kwanghua sp. nov. Zhu & He, bringing the number of this genus in Hainan Island to four. We conducted phylogenetic analyses with two mitochondrial genes (16S & Cytb) and two nuclear genes (RAG1 & C-MOS) to validate this new species. The new species is similar to G. hainanensis, but differs in the following characters: (1) middle section of the nuchal loop wide and posteriorly protracted, (2) wider body bands with dark markings, (3) yellow stripes on posterior side of humerus and femur, linked to the first and third body bands, respectively. The type specimens are deposited in the Museum of Biology, East China Normal University (ECNU).